Analysis Of Learning Obstacle On Fraction Material for Grade V Elementary School Students - Ratu, Elisa; Bambang Hermansah; Imelda Ratih Ayu (Journal of Practice Learning and Educational Development, 2025)
This study aims to analyze the learning obstacle experienced by fifth-grade students in understanding fraction material at SDN 231 Palembang. Fraction are a fundamental component of elementary mathematics education, yet many students still struggle to comprehend and solve problems involving fractional operations. This research employs a qualitative approach with a case study strategy. Data werw collected through diagnoctic tests, interviews with teachers and students, and documentation. the analysis revealed three types of learning obstacle: (1) Ontogenic Obstacle, releted to students’ mental readiness and foundational skills; (2) Didactical Obstacle, resulting from ineffective instructional strategies; and (3) Epistemological Obstacle, referring to students’ limited knowledge that is confined to specific contexts. This study provides insights into the difficulties students face in learning fractions and serves as a basis for developing more effective teaching strategied.